Modernism and the Occult - Bramhall, John 1594-1663 (London New York Palgrave Macmillan, 2015)
"Building on art-historian Bernard Smith's insights about modernism's debts to the high imperial occult and exotic, this book explores the transcultural, 'anti-modern vitalist', and magical-syncretic dimensions of the arts of the period 1880-1960. Avoiding simplistic hypotheses about 're-enchantment', it tracks the specifically modernist, not the occult revivalist or proto-New Age, manifestations of the occult-syncretic-exotic conglomerate. The focus is high empire, where the 'Buddhist' Schopenhauer cult and Theosophy, the last aided by Bergson, Nietzsche and neo-Vedanta, brought contrasting decreative-catastrophic and regenerative-utopian notes into the arts. Another instance of the Eastward turn in modernist esotericism, the Fifties 'Zen' vogue is also considered. This is the first overview of what modernists, as opposed to sectarian occultists, actually did with the occult. As such, it reframes the intellectual history of the modernist era, to present the occult/syncretic as an articulative idiom - a resource for making sense of the kaleidoscopic strangeness, fluidity and indeterminacy of modern life"--
Machine generated contents note:1. Empire and Occultism2. Modernist Interworlds3. Destruction-Creation: from Decadence to Dada4. Call to Order, Occultist Geopolitics, Spirit Wars 5. 'Zen' in the Second Abstraction6. Owning, Disowning and Trivializing the OccultNotesSelect BibliographyIndex.
Literaturangaben
Keywords: Occultism; Modernism (Art) -- Influence